Analisa Terjadinya Electrical Treeing Pada Isolator Komposit dengan Bahan Pengisi Serat Pelepah Nipah - Rahmat, Saepul; Prima Dewi, Riyani; Alimudin, Erna (P3M Politeknik Negeri Cilacap, 2024)
Technological developments in materials are increasingly evolving, one form of development is the type of composite insulation. One of the natural fiber composites currently available is a composite from palm fiber which provides increased dielectric strength. Partial discharge due to voids in the composite results in structures such as electrical treeing due to changes in the properties and morphology of the composite causing increased insulation failure and disrupting power distribution. This research tested the strength of Epoxy composite insulation and palm leaf ash filler. By combining these two materials, a complementary composite insulating material will be formed to prevent electrical treeing. The results of the research show that the composite insulating material with nipa palm fiber as filler has an average breakdown voltage value of 40 kV and is above the standard breakdown voltage value for medium voltage insulators of 30 kV. The addition of more and more palm leaf ash filling material will produce voids, thereby accelerating the occurrence of electrical treeing and decreasing the breakdown voltage of the insulation.